Reconsidérer la prospective de l’eau en Europe dans ses dimensions politiques - Sara Fernandez; Gabrielle Bouleau; Sébastien Treyer (Développement Durable et Territoires)
This article challenges the current dominant approach to planning the use of natural resources in the European Union. This approach addresses changes through the lens of the resource itself. Society is broadly conceived as a homogeneous force affecting the environment unless regulated by adequate governance. From the initial concept of impact, the Organization for Economic Cooperation and Development (OECD) and the European Environment Agency (EEA) have further developed the Driving forces-Pressures-State-Impact-Response (DPSIR) model which becomes hegemonic within European water planning. Using the example of a French watercourse, the Garonne River, we highlight the social contingency of the construction of water indicators. This example helps us to unpack neo-liberal premises and geographical biases of the DPSIR model. We propose to question this model by showing that several alternate DPSIR framings are possible on the Garonne. We discuss the added value of a plurality of framings to build contrasted futures, as opposed to the dominant approach which favours the participation of a plurality of actors.